Elevated levels of PAI-1 precede the occurrence of type 2 diabetes mellitus - Jenny Hernestål-Boman; Tina Öhman; Jan-Håkan Jansson; Marcus M. Lind; Olov Rolandsson; Ingvar A. Bergdahl; Lars Johansson (Diabetology & Metabolic Syndrome)
Abstract Aims Plasminogen activator inhibitor-1 (PAI-1) is the main inhibitor of the fibrinolytic system and is mainly secreted from adipose tissue. It is associated with cardiovascular disease and has also been considered a possible early risk marker for type 2 diabetes. Here, we present the results of a large prospective study investigating PAI-1 levels in relation to incident type 2 diabetes mellitus. Methods We conducted a prospective incident case-referent study within the Västerbotten Intervention Programme (VIP). Data on cardiovascular risk factors, fasting plasma glucose (FPG) and 2-hour plasma glucose (2-hPG) were collected at baseline health examination 1990–2005. Blood samples were collected and stored for future analyses. Participants were followed and 484 cases developed type 2 diabetes. Referents without type 2 diabetes were matched for sex, age, and year of participation, n = 484. Baseline plasma samples were analysed for PAI-1. Subgroup analysis was performed for 201 cases and 201 matched referents with normal baseline glucose levels (FPG < 6.1 and 2hPG < 8.9 mmol/L). Results Elevated baseline levels of PAI-1 were associated with incident type 2 diabetes after adjustments for BMI, family history of diabetes, smoking status, hypertension, FPG and 2hPG (PAI-1; OR = 1.87, 95% CI: 1.06–3.29). A similar result was shown in the subgroup analysis with 201 participants who had normal glucose levels at time of the health examination (PAI-1; OR = 2.68, 95% CI: 1.03–6.95). Conclusions Elevated PAI-1 levels in non-diabetic persons precede the manifestation of type 2 diabetes and can be detected before an elevation of FPG or 2-hPG is observed.